Physiological Consequences of Coronary Arteriolar Dysfunction and Its Influence on Cardiovascular Disease - Allaqaband, Hassan (Physiology (Bethesda), 2018)
To date, the major focus of diagnostic modalities and interventions to treat coronary artery disease has been the large epicardial vessels. Despite substantial data showing that microcirculatory dysfunction is a strong predictor of future adverse cardiovascular events, very little research has gone into developing techniques for in vivo diagnosis and therapeutic interventions to improve microcirculatory function. In this review, we will discuss the pathophysiology of coronary arteriolar dysfunction, define its prognostic implications, evaluate the diagnostic modalities available, and provide speculation on current and potential therapeutic opportunities.